Antitumor activity of edible fishes (Channa striata and Anabas testudineus) and gastropods (Helix aspersa and Pila virens) rudimentary mucus against HT-29 cell line and its biochemical properties - Elumalai Devan; Hemavathi Maduraiveeran; Kavitha Raja; Arulvasu Chinnasamy; Govindan Sivalingam; Sathya Balaji; Vinoth Neelakandan; Sharon Agnita; Murugan Rajaram (Journal of Basic and Applied Zoology)
Abstract Background The mucus from fish and gastropods contains a wide range of bioactive molecules with biomedical properties. The fish and gastropods were collected from Oragadam lake, Kanchipuram district, Tamil Nadu, India. In this study, we wanted to examine the anticancer potential of fish and gastropods mucus. The biochemical components of the crude mucus were screened. Results The biochemical analysis showed that the mucus of Anabas testudineus and Pila virens contained a high level of carbohydrates (2.8 and 1.5 mg/ml), the mucus of Channa striata contained a high level of lipids (0.9 mg/ml), and the mucus of Helix aspersa contained a high level of protein (1.3 mg/ml). The results showed morphological variations in the HT-29 cells upon treatment with crude mucus. Upon 24 h of gestation, the frozen cells began to shrink and seem round in shape. Using the MTT assay, the mucus crude extract was evaluated for its anticancer properties against the human colon cancer cell line (HT 29). The inhibitory concentration (IC50) was determined at 100 µg/ml after 24 h. Using specific staining techniques; fluorescent microscopy was utilized to examine the cell morphology and early and late apoptotic stages. Propidium iodide staining showed nuclear damage followed by DNA damage. This showed that the rudimentary mucus could prompt cell death and increased the number of fragments and mucus concentration, respectively. Conclusion This study showed that the edible or commercially important fish and gastropod mucus have potential anticancer activity against HT-29 cancer cells.